Dr. Michał Charytonowicz — Deep Plane Facelift — Warsaw - Charytonowicz, Michał (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Michał Charytonowicz, practicing in Warsaw, Poland. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002966; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; poland; warsaw